Data analysis in telecommunication services - Caiafa, Marcelo Dante (2023)
The data has become a main source of knowledge for organizations. Its adequate treatment allows to obtain valuable information. The professional link between university and industry is the goal of our academic work. It is intended to register an articulation project based on data analysis. It is an initiative based on a collaboration between a company and the academy. The aim is using the knowledge and skills of the students to improve the efficiency of the company by automating a process and at the same time bring computer engineering students closer to the productive environment. The work is based on Python and its libraries for data processing of a telecommunication services. The project is based on an exploratory, correlation and segmentation study of data processing for telecommunication services. The goal is to build a customer profile with high dropout potential. The work´s intention is to add value to decision makers in a data-based organization and verify the contribution that new tools can offer to students and teachers in the ICT sector (information and communication technologies).